Transformational Leadership Strategy of Madrasah Principals in Strengthening School-Based Management - Rohmad, Ali; Septiyaningsih, Putri; Mu’awanah, Elfi (LETIGES, 2026)
This study aims to examine the strategies of madrasah principals in strengthening the four dimensions of transformational leadership—idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration—within the implementation of School-Based Management (SBM) at MTsN 7 Tulungagung. This study employs a qualitative approach with a post-positivistic paradigm. Data were collected through participatory observation, semi-structured interviews, and documentation. Analysis techniques using data condensation, data display, and conclusion drawing, with validity ensured through triangulation and peer debriefing. The findings indicate that the principal integrates the madrasah's vision and mission into institutional programs, motivates educators through moral support and rewards, enhances teacher competence through training, provides adequate learning facilities, and addresses the individual needs of staff. These strategies demonstrate the central role of the principal in fostering a collaborative and value-based educational environment. The originality of this study lies in its comprehensive analysis of transformational leadership practices within the SBM framework in an Islamic junior high school context, highlighting the integration of IMTAQ and IPTEK values. However, this study is limited to a single case study, which may affect the generalizability of the findings.